2018
DOI: 10.1097/iae.0000000000001816
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Intraocular Retinoblastoma

Abstract: High-risk intraocular retinoblastoma is more common in Asian Indians compared with Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In a study of retinoblastoma patients from India and the United States of America, it was noted that Asian Indians had a fivefold greater risk of having optic nerve invasion and threefold greater risk of massive choroidal invasion compared with Americans. [ 23 ] In our study approximately 33% patients had optic nerve involvement.…”
Section: Discussionmentioning
confidence: 48%
“…In a study of retinoblastoma patients from India and the United States of America, it was noted that Asian Indians had a fivefold greater risk of having optic nerve invasion and threefold greater risk of massive choroidal invasion compared with Americans. [ 23 ] In our study approximately 33% patients had optic nerve involvement.…”
Section: Discussionmentioning
confidence: 48%
“…Studies from various countries have highlighted the importance of early diagnosis of RB and the implications of delayed treatment. Studies from Asia have shown that a delayed diagnosis of RB results in an advanced disease at presentation with poorer chances of globe salvage [11,12]; studies from the United Kingdom and India have revealed higher chances of high-risk histopathological features with subsequent need for adjuvant chemotherapy [13,14]; a study from Brazil has shown increased mortality due to increased lag time [15]; a study from Switzerland has shown that reduced lag time is associated with early stage of the disease at presentation [16]; and a study from the Netherlands has shown correlation between early diagnosis and decreased mortality and blindness [17]. Herein, we prospectively studied the lag time between onset of symptoms and diagnosis of RB in 10 countries on five continents from 1 January 2019 to 31 December 2019 and compared the results based on country income levels to assess the causes of increased lag time and its effect on the patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most common pediatric malignant cancer of the eye and can easily lead to the loss of either sight or the eyeball and even death during early childhood [2]. The incidence and degree of malignancy of retinoblastoma are higher in developing countries than those in developed countries; moreover, cure rates remain unsatisfactory in developing countries, with relatively high morbidity and mortality, lower rates of eye salvage and higher rates of extraocular dissemination [35]. Survival rates in high-income countries can be greater than 95%, while the global survival rate is less than 30% [2].…”
Section: Introductionmentioning
confidence: 99%